Odpowiedź :
Odpowiedź:
[tex]a)\\\\\frac{3-2x}{4}=\frac{7-3x}{6}\\\\6(3-2x)=4(7-3x)\\\\18-12x=28-12x\\\\-12x+12x=28-18\\\\0=10\\\\R\'ownanie\ \ sprzeczne\ \ nie\ \ ma\ \ rozwiazania\\\\\\b)\\\\\frac{5-x}{3}+\frac{2x}{3}=\frac{x}{2}\ \ /*6\\\\2(5-x)+4x=3x\\\\10-2x+4x=3x\\\\10+2x=3x\\\\2x-3x=-10\\\\-x=-10\ \ /*(-1)\\\\x=10[/tex]
[tex]c)\\\\1-\frac{2x+7}{4}=5-\frac{1}{2}x\ \ /*4\\\\4-(2x+7)=20-2x\\\\4-2x-7=20-2x\\\\-3-2x=20-2x\\\\-2x+2x=20+3\\\\0=23\\\\R\'ownanie\ \ sprzeczne\ \ nie\ \ ma\ \ rozwiazania\\\\\\d)\\\\2(5-\frac{x-3}{2})+2x=0\\\\10-(x-3)+2x=0\\\\10-x+3+2x=0\\\\x+13=0\\\\x=-13[/tex]
[tex]e)\\\\\frac{8x-5}{4}-(x-\frac{3}{4})=x-\frac{1}{2}\\\\\frac{8x-5}{4}-x+\frac{3}{4}=x-\frac{1}{2}\ \ /*4\\\\8x-5-4x+3=4x-2\\\\4x-2=4x-2\\\\4x-4x=-2+2\\\\0=0\\\\R\'ownanie\ \ to\.zsamo\'sciowe\ \ ma\ \ niesko\'nczenie\ \ wiele\ \ rozwiaza\'n\\\\\\f)\\\\16-\frac{6-9x}{3}=7(1+3x)-19x\\\\16-(2-3x)=7+21x-19x\\\\16-2+3x=7+2x\\\\14+3x=7+2x\\\\3x-2x=7-14\\\\x=-7[/tex]